2020
DOI: 10.1038/s41467-020-20235-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiology reveals transmission patterns and dynamics of SARS-CoV-2 in Aotearoa New Zealand

Abstract: New Zealand, a geographically remote Pacific island with easily sealable borders, implemented a nationwide ‘lockdown’ of all non-essential services to curb the spread of COVID-19. Here, we generate 649 SARS-CoV-2 genome sequences from infected patients in New Zealand with samples collected during the ‘first wave’, representing 56% of all confirmed cases in this time period. Despite its remoteness, the viruses imported into New Zealand represented nearly all of the genomic diversity sequenced from the global vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 44 publications
2
88
0
Order By: Relevance
“…We obtained 212 complete genomes (Fig 1B), mostly from samples with higher viral loads (Fig 1B). Consensus genomes had a median of 7 substitutions relative to the Wuhan-Hu-1/2019 reference sequence (range [4][5][6][7][8][9][10][11][12]. Phylogenetic analysis of whole consensus genomes identified 10 unique evolutionary lineages in our cohort (lineages determined by the PANGOLIN system, see Methods; Fig 1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained 212 complete genomes (Fig 1B), mostly from samples with higher viral loads (Fig 1B). Consensus genomes had a median of 7 substitutions relative to the Wuhan-Hu-1/2019 reference sequence (range [4][5][6][7][8][9][10][11][12]. Phylogenetic analysis of whole consensus genomes identified 10 unique evolutionary lineages in our cohort (lineages determined by the PANGOLIN system, see Methods; Fig 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Over the course of the SARS-CoV-2 pandemic, whole genome sequencing has been widely used to characterize patterns of broad geographic spread, transmission in local clusters, and the spread of specific viral variants [1][2][3][4][5][6]. Early reports demonstrated that SARS-CoV-2 exhibits genetic diversity within infected hosts, but this has been less studied than consensus-level genomic diversity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Genomes of the first 649 viral isolates collected in New Zealand show that only 19% of introductions were estimated to infect more than one other person. 9 Therefore, counts of border failures are sensitive to how they are identified and defined. Indeed, with increased testing (eg, testing of people after leaving quarantine on day 16 as is now common in Australia), we may be detecting breaches that previously went undetected.…”
Section: Discussionmentioning
confidence: 99%
“…During 2020, laboratories and institutes around the world produced and shared over 300000 whole SARS-CoV-2 genome sequences in the GISAID repository ( 1 ), providing an unparalleled data set that permits detailed analyses of virus transmission and dissemination. These achievements have provided insights into the sources of SARS-CoV-2 importation and early transmission dynamics in individual countries and geographical regions ( 2 5 ), and have enabled the exploration of viral transmission history at a global scale ( 6 ). Phylogenetic methods, including molecular clock models and phylogeographic and phylodynamic methods, are now used routinely to analyse such genomic data from emerging outbreaks ( 7 ).…”
Section: Introductionmentioning
confidence: 99%